Characterization of the Physicochemical Properties of Lignocellulosic Plant Residue - Pooja M Eranna , Madhusudhan Nayak C , Hanumantharaju K N , Anusha M B , Chennappa Gurikar , Lokesh A.C (South Eastern European Journal of Public Health, 2025)
In this research, we investigated a range of plant-based materials, including- Banana Leaf, Pineapple crown, Rice husk, Baggas, Corn husk, as potential for biodegradable cutlery. The materials aimed to optimize raw material by evaluating chemical properties of natural biomass materials. Characterized Including Lignin, Cellulose, Nitrogen, Moisture and Ash content The study demonstrates the viability of agricultural waste-derived composites for durable, fully biodegradable cutlery. Optimized formulations balance functional performance with rapid environmental degradation, supporting circular economy goals. The study demonstrates the viability of agricultural waste-derived composites for durable, fully biodegradable cutlery, balancing functional performance with rapid environmental degradation and supporting circular economy goals.